Controllable synthesis of efficient Ru-doped PtSn alloy nanoplate electrocatalysts for methanol oxidation reaction. (1st September 2022) - Wang, Yanyun; Zhao, Xiwang; Deng, Qinghua; Bao, Jiehua; Sheng, Xiaoli; Huang, Yuzhong; Zhang, Yiwei; Zhou, Yuming
Abstract: Platinum (Pt) is considered as the preferred metal catalyst for methanol oxidation reactions. However, the application prospects of Pt catalysts are limited due to the inherent scarcity and cost. Enabling a trace amount of Pt to exert satisfactory catalytic activity and durability has become a key issue in designing electrocatalysts. Here, Ru-doped PtSn alloy nanoplates (PtSn@Ru NP) with an average particle size of less than 5 nm were controllably synthesized by adjusting the Pt–Sn atomic ratio. Compared with Ru-doped PtSn alloy nanospheres (PtSn@Ru NS/C, 714.7 mA/mgPt ), PtSn bimetallic nanoplates (PtSn NP/C, 880.2 mA/mgPt ) and commercial Pt/C (299.6 mA/mgPt ), the prepared PtSn@Ru NP/C (1105.1 mA/mgPt ) exhibited an extraordinary methanol oxidation mass activity. Furthermore, the peak oxidation current retention of PtSn@Ru NP/C was as high as at 87.5% after 1000 accelerated durability tests. The significantly enhanced catalytic performance and durability were attributed to the synergistic effect of the alloy components and morphological advantages. This work has led us to think more deeply about the constitutive relationship between structure and performance. Graphical abstract: Image 1 Highlights: Ru-doped PtSn alloy nanoplates with uniform dimensions (5 nm) were prepared. Ru doping promoted the efficient conversion of the intermediate products. The synergistic effect of Sn and Pt improved the stability of the catalyst. PtSn@Ru NP/C exhibited excellent methanol oxidation mass activity (1105.1 mA/mgPt ).